Thermoplastic carbon fiber composite material and preparation method thereof

By recycling and modifying carbon fiber waste, the enhanced nylon 6 composite material is prepared, which solves the problem of carbon fiber waste not being effectively utilized, and achieves efficient utilization of resources and environmental friendliness.

CN119592060APending Publication Date: 2025-03-11CHONGQING NAKEN ZHONGYI NEW MATERIALS CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411921278.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The waste generated in carbon fiber production and processing has not been effectively utilized, resulting in waste of resources and environmental pollution.

Method used

By sizing, drying and chopping the recovered carbon fibers, carbon fiber raw materials are prepared and mixed with modified nylon 6 to prepare reinforced nylon 6 pellets or powders, and curing them by injection molding or 3D printing to make a composite material with high performance.

Benefits of technology

It improves the strength and conductivity of thermoplastic materials, reduces resistance, achieves anti-static effects, and avoids waste of resources through recycling and reuse, which has cost advantages and environmental significance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005208068850000081
    Figure BDA0005208068850000081
  • Figure BDA0005208068850000091
    Figure BDA0005208068850000091
  • Figure BDA0005208068850000101
    Figure BDA0005208068850000101
Patent Text Reader

Abstract

The invention relates to the technical field of thermoplastic composite materials, in particular to a thermoplastic carbon fiber composite material which is prepared by sizing and drying recycled carbon fibers to obtain a carbon fiber raw material and then adding modified nylon into the carbon fiber raw material. According to the invention, the carbon fibers are recycled and mixed with the modified nylon 6 to prepare reinforced nylon 6 granules, the reinforced nylon 6 granules are used as a thermoplastic curing raw material, the reinforced nylon 6 granules are subjected to injection molding or 3D printing curing molding to prepare different products, and in the reinforced nylon 6, due to the carbon fibers, the carbon fibers in the prepared products have good mechanical properties, so that the strength of the product is greatly improved. And the performance of the product can be comprehensively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of thermoplastic composite materials, and in particular to a thermoplastic carbon fiber composite material and a preparation method thereof. Background Art

[0002] As the share of carbon fiber materials in the automotive, aerospace and other markets increases year by year, the amount of scrapped materials in carbon fiber production and processing also increases, and the recycling and reuse of carbon fiber has become a trend. The composite materials produced by blending thermoplastic materials with carbon fiber can improve the strength of the thermoplastic material itself and reduce electrical resistance. At the same time, the recycling and reuse of carbon fiber will also have certain price advantages. Summary of the invention

[0003] In view of the above-mentioned shortcomings of the prior art, the present invention provides a thermoplastic carbon fiber composite material and a preparation method thereof for the recycling of carbon fiber waste in carbon fiber production and processing, thereby improving the strength of the thermoplastic material itself, reducing resistance, and achieving the performance of anti-static and conductive materials.

[0004] Technical Solution

[0005] To achieve the above objectives, the present invention is implemented through the following technical solutions:

[0006] The present invention provides a thermoplastic carbon fiber composite material, which is prepared by sizing, drying and chopping recycled carbon fibers to obtain carbon fiber raw materials, and then adding modified nylon to the carbon fiber raw materials;

[0007] The modified nylon comprises at least one of nylon 6, a compatibilizer, an antioxidant, a coupling agent, and a lubricant, and a mixture of the above.

[0008] Among them, the recycled carbon fiber includes any one or more of the scrapped carbon fiber prepregs in the carbon fiber production process and at the end of its service life, scrapped carbon fiber parts, carbon fiber yarns after high-temperature cracking, winding defective products, remaining yarn tails, carbon fiber fabric scraps, and fabric scraps.

[0009] Furthermore, by weight percentage, the recycled carbon fiber accounts for 90% to 99% of the carbon fiber raw material, and the sizing agent accounts for 1% to 10%; the sizing agent is at least one or more of polyamide, polyurethane, epoxy vinyl ester, and epoxy resin emulsion.

[0010] Preferably, by weight percentage, the recycled carbon fiber accounts for 97% and the sizing agent accounts for 3% in the carbon fiber raw material.

[0011] Preferably, the sizing agent is polyurethane or epoxy resin emulsion, wherein, most preferably, the manufacturer and model of the polyurethane used in the sizing agent is Chongqing Haikemu New Material Technology Co., Ltd. / C4010; the manufacturer and model of the epoxy resin emulsion used in the sizing agent is Dongguan Guangtong Chemical Products Co., Ltd. / BH-6204.

[0012] Furthermore, in the composite material, by weight percentage, the carbon fiber raw material accounts for 20% to 60%, and the modified nylon accounts for 26-76%.

[0013] Furthermore, in terms of weight percentage, the composite material comprises 20% to 60% carbon fiber raw material, 26% to 72% nylon 6, 3% to 10% compatibilizer, 0.1% to 5% antioxidant, 0.5% to 6% coupling agent, and 0.2-5% lubricant.

[0014] Preferably, by weight percentage, the composite material comprises 20% to 50% carbon fiber raw material, 45% to 72% nylon 6, 3.5% to 5.6% compatibilizer, 0.45% to 0.72% antioxidant, 0.7% to 1.12% coupling agent, and 0.35% to 0.56% lubricant. Among them, the compatibilizer is maleic anhydride grafted POE; the antioxidant uses 1,6-hexamethylenebis[3,5-bis(1,1-dimethylethyl)-4-hydroxybenzene propionamide] and tris(2,4-di-tert-butylbenzene) phosphite, and the weight ratio of 1,6-hexamethylenebis[3,5-bis(1,1-dimethylethyl)-4-hydroxybenzene propionamide] to tris(2,4-di-tert-butylbenzene) phosphite is 1:2; the coupling agent uses 3-aminopropyltriethoxysilane or (2,3-epoxypropoxy)propyltrimethoxysilane; the lubricant uses zinc stearate or aluminum distearate.

[0015] Preferably, by weight percentage, in the composite material, 20% to 50% carbon fiber raw material, 45% to 72% nylon 6, 0.7% to 1.12% 3-aminopropyl triethoxysilane, 3.5% to 5.6% maleic anhydride grafted POE, 0.15% to 0.24% 1,6-hexylenebis[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenylpropionamide], 0.3% to 0.48% tris(2,4-di-tert-butylphenyl) phosphite, 0.35%-0.56% zinc stearate. The composite material prepared by the above components has a tensile strength of >60Mpa, a tensile modulus of greater than 4Gpa, a flexural strength of greater than 87Mpa, and a flexural modulus of greater than 3Gpa.

[0016] Preferably, by weight percentage, the composite material comprises 20% carbon fiber raw material, 72% nylon 6, 1.12% 3-aminopropyltriethoxysilane, 5.6% maleic anhydride grafted POE, 0.24% 1,6-hexamethylenebis[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenylpropionamide], 0.48% tris(2,4-di-tert-butylphenyl) phosphite, and 0.56% zinc stearate.

[0017] Preferably, by weight percentage, the composite material comprises 30% carbon fiber raw material, 63% nylon 6, 0.98% 3-aminopropyltriethoxysilane, 4.90% maleic anhydride grafted POE, 0.21% 1,6-hexamethylenebis[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenylpropionamide], 0.42% tris(2,4-di-tert-butylphenyl) phosphite, and 0.49% zinc stearate.

[0018] Preferably, by weight percentage, the composite material comprises 40% carbon fiber raw material, 54% nylon 6, 0.84% ​​3-aminopropyltriethoxysilane, 4.20% maleic anhydride grafted POE, 0.18% 1,6-hexamethylenebis[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenylpropionamide], 0.36% tris(2,4-di-tert-butylphenyl) phosphite, and 0.42% zinc stearate.

[0019] Preferably, by weight percentage, the composite material comprises 50% carbon fiber raw material, 45% nylon 6, 0.7% 3-aminopropyltriethoxysilane, 3.5% maleic anhydride grafted POE, 0.15% 1,6-hexamethylenebis[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenylpropionamide], 0.3% tris(2,4-di-tert-butylphenyl) phosphite, and 0.35% zinc stearate.

[0020] Furthermore, the compatibilizer is a maleic anhydride grafted polymer, and the maleic anhydride grafted polymer is at least one or more of maleic anhydride grafted POE, maleic anhydride grafted PS, and maleic anhydride grafted PE; preferably, the compatibilizer is maleic anhydride grafted POE.

[0021] The antioxidant includes one or two of 1,6-hexamethylenebis[3,5-bis(1,1-dimethylethyl)-4-hydroxybenzenepropionamide] and tris(2,4-di-tert-butylbenzene) phosphite; preferably, the antioxidant uses 1,6-hexamethylenebis[3,5-bis(1,1-dimethylethyl)-4-hydroxybenzenepropionamide] and tris(2,4-di-tert-butylbenzene) phosphite, and the weight ratio of 1,6-hexamethylenebis[3,5-bis(1,1-dimethylethyl)-4-hydroxybenzenepropionamide] to tris(2,4-di-tert-butylbenzene) phosphite is 1:2.

[0022] The coupling agent is one or both of (2,3-epoxypropoxy)propyltrimethoxysilane and 3-aminopropyltriethoxysilane; preferably, the coupling agent is 3-aminopropyltriethoxysilane or (2,3-epoxypropoxy)propyltrimethoxysilane.

[0023] The lubricant is at least one of AT-ethylene bis stearic acid amide, zinc stearate, octadecanol, aluminum distearate, ethylene bis stearamide, and ethylene bis stearamide. Preferably, the lubricant is zinc stearate or aluminum distearate.

[0024] A method for preparing a thermoplastic carbon fiber composite material comprises the following steps:

[0025] (1) sizing the recovered carbon fiber, and then drying and chopping the sizing carbon fiber to obtain a carbon fiber raw material;

[0026] (2) Nylon 6, a compatibilizer, an antioxidant, a coupling agent, and a lubricant are mixed, and then the carbon fiber is mixed with the modified nylon to obtain reinforced nylon 6 pellets or powder; and then the mixture is mixed and extruded through a twin-screw.

[0027] Furthermore, the specific operation of step (1) is as follows:

[0028] S1, soaking the recycled carbon fiber in a sizing agent;

[0029] S2, through the vibration of the vibrating screen and the air flow, the carbon fiber yarn is dispersed and fully infiltrated with the sizing agent;

[0030] S3, passing the carbon fiber yarn impregnated with the sizing agent through a rubber squeezing roller to squeeze out excess sizing agent;

[0031] S4, drying the sizing carbon fiber for 5-20 minutes, and then cutting it into fibers of 0.1-0.3 mm to obtain a carbon fiber raw material;

[0032] Wherein, in step S1, before re-sizing the carbon fiber, if there is residual sizing agent on the recovered carbon fiber, the recovered carbon fiber is first desized at high temperature to remove the original sizing agent; and then the operation steps S1-S3 are performed.

[0033] Furthermore, the twin-screw extrusion temperature in step (2) is 240-300°C.

[0034] Furthermore, in step S1, the high temperature desizing temperature is 400-800° C., and the time is 20-40 minutes.

[0035] Compared with the known public technology, the technical solution provided by the present invention has the following beneficial effects: the present invention recycles carbon fiber and mixes it with modified nylon 6 to produce reinforced nylon 6 pellets, which are used as thermoplastic curing raw materials. The reinforced nylon 6 pellets are injection molded or 3D printed for curing and molding to produce different products. In addition, since the reinforced nylon 6 contains carbon fiber, the carbon fiber in the manufactured products can comprehensively improve the performance of the products. With the popularization of carbon fiber parts, recycling and reuse can avoid waste of resources and be environmentally friendly. The cost of recycled carbon fiber is much lower than that of new carbon fiber. Compared with nylon 6 pellets using new carbon fiber as reinforcing material, the manufactured products have obvious cost advantages, thereby forming a closed loop for the development of the entire carbon fiber industry, which is beneficial to the development of the entire carbon fiber industry. DETAILED DESCRIPTION

[0036] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] The present invention will be further described below in conjunction with the embodiments.

[0038] The manufacturers and brands of raw materials in the embodiments and comparative examples are as follows:

[0039] 12K / T300 cotton-like PAN carbon fiber: Weiken New Materials Co., Ltd.

[0040] Polyurethane: Chongqing Haikemu New Material Technology Co., Ltd. / C4010;

[0041] Epoxy resin: Dongguan Guangtong Chemical Products Co., Ltd. / BH-6204;

[0042] Nylon 6: Baling Petrochemical / YH800;

[0043] Maleic anhydride grafted POE: Shenyang Ketong Plastic Technology Co., Ltd. / KT-9.

[0044] (I) Preparation of carbon fiber composite materials

[0045] Experiment 1:

[0046] A preparation step of a thermoplastic carbon fiber composite material is as follows:

[0047] (1) The materials used are recycled materials from the processing of carbon fiber felt.

[0048] (2) Resizing the carbon fiber includes the following steps:

[0049] S1: soaking the recycled carbon fiber into sizing agent;

[0050] S2: The carbon fiber yarn is dispersed and fully impregnated with the sizing agent through vibration of the vibrating screen and air flow;

[0051] S3: passing the carbon fiber yarn impregnated with the sizing agent through a rubber squeezing roller to squeeze out excess sizing agent;

[0052] S4: drying the sized carbon fiber for 5 minutes and chopping it into pieces of 0.3-0.4 mm to obtain a carbon fiber raw material;

[0053] (3) nylon 6, a compatibilizer, an antioxidant, a coupling agent, and a lubricant are blended to prepare modified nylon; the carbon fiber raw material and the modified nylon are mixed in the middle section of a twin-screw;

[0054] (4) Reinforced nylon 6 pellets or powder are prepared, mixed and extruded by a twin screw at an extrusion temperature of 260°C.

[0055] Examples 1-4 are all prepared by the above-mentioned preparation method, and in step (1), 12K / T300 cotton-like PAN-based carbon fiber is used, and in step (2), 12K / T300 cotton-like PAN-based carbon fiber is mixed with polyurethane for sizing, and the sizing agent content is 3%.

[0056] The difference between Examples 1-4 is only the different proportions of modified nylon and carbon fiber raw materials. The specific proportions of the components are shown in the following table:

[0057]

[0058] Experiment 2:

[0059] A preparation step of a thermoplastic carbon fiber composite material is as follows:

[0060] (1) The materials used are recycled materials from the processing of carbon fiber felt.

[0061] (2) Resizing the carbon fiber includes the following steps:

[0062] S1: soaking the recycled carbon fiber into sizing agent;

[0063] S2: The carbon fiber yarn is dispersed and fully impregnated with the sizing agent through vibration of the vibrating screen and air flow;

[0064] S3: passing the carbon fiber yarn impregnated with the sizing agent through a rubber squeezing roller to squeeze out excess sizing agent;

[0065] S4: drying the sized carbon fiber for 5 minutes and chopping it into pieces of 0.3-0.4 mm to obtain a carbon fiber raw material;

[0066] (3) nylon 6, a compatibilizer, an antioxidant, a coupling agent, and a lubricant are blended to prepare modified nylon; the carbon fiber raw material and the modified nylon are mixed in the middle section of a twin-screw;

[0067] (4) Reinforced nylon 6 pellets or powder are prepared, mixed and extruded by a twin screw at an extrusion temperature of 260°C.

[0068] Examples 5-8 are all prepared using the above-mentioned preparation method, and in step (1), 12K / T300 cotton-like PAN-based carbon fiber is used, and in step (2), 12K / T300 cotton-like PAN-based carbon fiber is mixed with epoxy resin emulsion for sizing, and the sizing agent content is 3%.

[0069] The difference between Examples 5-8 is only the different proportions of modified nylon and carbon fiber raw materials. The specific proportions of the components are shown in the following table:

[0070]

[0071] Comparison 3:

[0072] Comparative Example 1:

[0073] The only difference from Example 1 is that no compatibilizer is added; the specific composition ratio is shown in the following table:

[0074]

[0075] Comparative Example 2:

[0076] The only difference from Example 1 is that no coupling agent is added; the specific composition ratio is shown in the following table:

[0077]

[0078] Comparative Example 3:

[0079] The only difference from Example 1 is that no lubricant is added; the specific composition ratio is shown in the following table:

[0080]

[0081] Comparative Example 4:

[0082] The only difference from Example 1 is that the carbon fiber raw material ratio is 70%; the specific component ratios are shown in the following table:

[0083]

[0084] (II) The performance test results are as follows:

[0085] (1) Test standards

[0086] Tensile strength: measured using standard ISO 527;

[0087] Tensile modulus: measured using standard ISO 527;

[0088] Flexural strength: measured using standard ISO 178;

[0089] Flexural modulus: measured using standard ISO 178;

[0090] Surface resistance: measured using standard IEC62631-3-1;

[0091] Surface resistivity: measured using standard IEC62631-3-1.

[0092] (2) Test results

[0093] The performance test results of the composite materials prepared in Examples 1-4 are shown in Table 1:

[0094] Table 1

[0095] Test items unit PA6 Example 1 Example 2 Example 3 Example 4 Tensile Strength Mpa 54.8 60.8 73.4 83.2 84.2 Tensile modulus GPa / 5.13 8.42 9.54 11.42 Bending Strength Mpa 86.6 88.0 106.8 122.7 125.6 Flexural modulus GPa 2.09 3.50 5.06 6.92 8.43 Surface resistance Ω 3.00E+11 3.00E+04 6.00E+01 2.00E+01 1.20E+01 Surface resistivity Ω 2.40E+13 1.78E+05 3.56E+02 1.19E+02 7.13E+01

[0096] The performance test results of the composite materials prepared in Examples 5-8 are shown in Table 2:

[0097] Table 2

[0098] Test items unit PA6 Example 5 Example 6 Example 7 Example 8 Tensile Strength Mpa 54.8 68.64 72.37 84.91 87.23 Tensile modulus GPa / 4.37 5.52 8.53 11.83 Bending Strength Mpa 86.6 102.61 107.31 123.13 131.62 Flexural modulus GPa 2.09 3.79 4.24 6.57 9.87 Surface resistance Ω 3.00E+11 1.00E+06 1.00E+02 3.00E+01 2.00E+01 Surface resistivity Ω 2.40E+13 5.94E+06 5.94E+02 1.78E+02 1.19E+02

[0099] The performance test results of the composite materials prepared in Comparative Examples 1-4 are shown in Table 3:

[0100] Table 3

[0101] Test items unit Example 1 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Tensile Strength Mpa 60.8 32.22 23.37 69.41 32.95 Tensile modulus GPa 5.13 5.02 2.75 4.12 7.69 Bending Strength Mpa 88.0 39.77 29.7 83.88 38.9 Flexural modulus GPa 3.50 4.04 1.53 2.33 4.99 Surface resistance Ω 3.00E+04 3.00E+04 3.00E+04 1.00E+06 1.00E+01 Surface resistivity Ω 1.78E+05 1.78E+05 1.78E+05 5.94E+06 5.94E+01

[0102] The present invention recycles carbon fiber and mixes it with modified nylon 6 to prepare reinforced nylon 6 pellets. As a thermoplastic curing raw material, the reinforced nylon 6 pellets are injection molded or 3D printed for curing and forming to prepare different products. In addition, since the reinforced nylon 6 contains carbon fiber, the carbon fiber in the manufactured product can comprehensively improve the performance of the product. With the popularization of carbon fiber parts, recycling and reuse can avoid waste of resources and be environmentally friendly. The cost of recycled carbon fiber is much lower than that of new carbon fiber. Compared with nylon 6 pellets using new carbon fiber as a reinforcing material, the manufactured product has an obvious cost advantage, thereby forming a closed loop for the development of the entire carbon fiber industry, which is beneficial to the development of the entire carbon fiber industry.

[0103] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the protection scope of the technical solutions of the embodiments of the present invention.

Claims

1. A thermoplastic carbon fiber composite material, characterized in that: The carbon fiber raw material is obtained by sizing, drying and chopping the recycled carbon fiber, and then adding modified nylon to the carbon fiber raw material to prepare it; The modified nylon comprises at least one of nylon 6, a compatibilizer, an antioxidant, a coupling agent, and a lubricant, and a mixture of the above.

2. A thermoplastic carbon fiber composite material according to claim 1, characterized in that: In terms of weight percentage, the carbon fiber raw material comprises 90% to 99% recycled carbon fiber and 1% to 10% sizing agent; the sizing agent is at least one or more of polyamide, polyurethane, epoxy vinyl ester and epoxy resin emulsion.

3. The thermoplastic carbon fiber composite material according to claim 1, characterized in that: In terms of weight percentage, in the composite material, the carbon fiber raw material accounts for 20% to 60%, and the modified nylon accounts for 26-76%.

4. The thermoplastic carbon fiber composite material according to claim 1, characterized in that: In terms of weight percentage, the composite material comprises 20% to 60% carbon fiber raw material, 26% to 72% nylon 6, 3% to 10% compatibilizer, 0.1% to 5% antioxidant, 0.5% to 6% coupling agent, and 0.2% to 5% lubricant.

5. The thermoplastic carbon fiber composite material according to claim 1, characterized in that: The compatibilizer is a maleic anhydride grafted polymer, and the maleic anhydride grafted polymer is at least one or more of maleic anhydride grafted POE, maleic anhydride grafted PS, and maleic anhydride grafted PE; The antioxidant includes one or two of 1,6-hexamethylenebis[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenylpropionamide] and tris(2,4-di-tert-butylphenyl)phosphite; The coupling agent is one or two of (2,3-epoxypropoxy)propyltrimethoxysilane and 3-aminopropyltriethoxysilane; The lubricant is at least one or more of AT-ethylene bisstearic acid amide, zinc stearate, octadecanol, aluminum distearate, ethylene bisstearylamide, and ethylene bisstearic acid amide.

6. A method for preparing a thermoplastic carbon fiber composite material as claimed in claim 1, characterized in that: It includes the following steps: (1) sizing the recovered carbon fiber, and then drying and chopping the sizing carbon fiber to obtain a carbon fiber raw material; (2) Nylon 6, a compatibilizer, an antioxidant, a coupling agent, and a lubricant are mixed, and then the carbon fiber is mixed with the modified nylon to obtain reinforced nylon 6 pellets or powder; and then the mixture is mixed and extruded through a twin-screw.

7. The method for preparing a thermoplastic carbon fiber composite material according to claim 6, characterized in that: The specific operation of step (1) is as follows: S1, soaking the recycled carbon fiber in a sizing agent; S2, through the vibration of the vibrating screen and the air flow, the carbon fiber yarn is dispersed and fully infiltrated with the sizing agent; S3, passing the carbon fiber yarn impregnated with the sizing agent through a rubber squeezing roller to squeeze out excess sizing agent; S4, drying the sizing carbon fiber for 5-20 minutes, and then cutting it into fibers of 0.1-0.3 mm to obtain a carbon fiber raw material; Wherein, in step S1, before re-sizing the carbon fiber, if there is residual sizing agent on the recovered carbon fiber, the recovered carbon fiber is first desized at high temperature to remove the original sizing agent; and then the operation steps S1-S3 are performed.

8. The method for preparing a thermoplastic carbon fiber composite material according to claim 6, characterized in that: The twin-screw extrusion temperature in step (2) is 240-300°C.

9. The method for preparing a thermoplastic carbon fiber composite material according to claim 7, characterized in that: In step S1, the high temperature desizing temperature is 400-800°C and the time is 20-40 minutes.